(untitled) (Research, Society and Development, 2021)
Introduction: Cardiac surgeries are complex therapies that involve changes in the subject’s life. These changes imply changes in routine, self-esteem and self-image, especially in women. Occupational Therapy, which has the ability to assess and understand the subject in all contexts in which it is inserted, helps women in post-cardiac surgery. Objective: To understand the meanings attributed by women to the scar resulting from open heart surgery, under an occupational therapeutic perspective. Methodology: This is a descriptive and exploratory research, with a qualitative approach. It was performed at the Dr. Carlos Alberto Studart Gomes hospital - Hospital do Coração de Messejana, in Fortaleza, Ceará, Brazil, from October 2020 to January 2021. Five women who underwent open heart surgery, participated in the study. between 23 and 50 years old. The study on screen had the technique of collecting information as an individual and structured interview and as a method of analysis the content, in the thematic analysis modality. Results: The research generated four nuclei of meaning for a broader discussion, namely: The stigma of heart disease; Spiritual support; The fear of dependence on ADLs; The resignification of the scar. Conclusion: The women participating in the research showed a resilience of paramount importance, where they understood that the body is their temple, which needs to be recognized and taken care of.